D3.5 - Framework for implementing alternative credit schemes and digital social currencies - LUCARELLI, Stefano; GIULIANI, Alfonso (country:GB, 2015)
This deliverable documents the state of the art of legal frameworks of implementation both in general, but also particularly for D-CENT Digital Social Currency experiments with pilot communities in Spain, Iceland, Finland and the use case in Italy. The richness in contexts of the various pilots is remarkable and is being taken into account as Freecoin software development and systems are rolled out in the last phases of the project. At a glance, only the Spanish and Icelandic regulatory contexts are detailed enough to allow for experimentation within clear boundaries. . In Iceland there is only a single article that remands to the prohibition to issue bonds to the bearer outside the national banking system. Conversely, in Finland, rules are absent, although digital alternative and complementary currencies are not considered as illegal, they just exist in the informal economy. Finally, Italy is on its way to processing regulation in both the legislative and executive. Hence, Freecoin implementation will have to take into account these differences while promoting lawful operations in each pilot specific context in order to empower communities with a long-term viable framework of implementation.